1977
DOI: 10.3406/bagf.1977.4977
|View full text |Cite
|
Sign up to set email alerts
|

Y a-t-il eu capture du Niger ?

Abstract: Résumé. - L'hypothèse d'une capture récente du Niger près de Taoussia est remise en cause pour trois raisons : l'improbabilité du creusement d'un défilé si important par le fleuve dans une roche très dure ; l'existence d'une vieille topographie cuirassée d'âge Plio-Pléistocène ( ?) très proche de l'actuelle ; enfin une nouvelle interprétation de l'évolution morphologique quaternaire de la Vallée.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The Niger River elbow region in between the inland delta and the Iullemmeden basin (Figure ) has been surveyed by Beaudet et al . [] and Michel []. Those authors have shown that the S2 ferricrete capping the mesas of the region (i.e., the relicts of the “fundamental topography” of Beaudet et al .…”
Section: Geomorphic Configuration Along Key Portions Of the Drainagesupporting
confidence: 53%
See 4 more Smart Citations
“…The Niger River elbow region in between the inland delta and the Iullemmeden basin (Figure ) has been surveyed by Beaudet et al . [] and Michel []. Those authors have shown that the S2 ferricrete capping the mesas of the region (i.e., the relicts of the “fundamental topography” of Beaudet et al .…”
Section: Geomorphic Configuration Along Key Portions Of the Drainagesupporting
confidence: 53%
“…Those authors have shown that the S2 ferricrete capping the mesas of the region (i.e., the relicts of the “fundamental topography” of Beaudet et al . []) systematically dips toward the modern river and cement alluvial gravels in the vicinity of its course, arguing for its antiquity. Fieldwork also led to the same conclusion for the Tilemsi River, a tributary of the Niger draining the western flank of the Adrar des Ifoghas massif [ Beaudet et al , ] (Figure ).…”
Section: Geomorphic Configuration Along Key Portions Of the Drainagementioning
confidence: 99%
See 3 more Smart Citations